FLUOROSCOPY TIME DURING CARDIAC CATHETERIZATION PROCEDURES USING THE RADIAL AND FEMORAL ROUTES - Usman, Ahmad; Hussain, Fida; Iqbal, Tahir; Tuyyab, Farhan (Journal of Ayub Medical College Abbottabad, 2015)
Background: Use of trans-radial route for cardiac catheterization is on the rise but is associated with increased radiation exposure to the operator. Our aim was to compare the radiation exposure, by taking fluoroscopy time (FT) as a surrogate of radiation exposure, to the operator with femoral and radial routes. Methods: This prospective observational study was carried out at Army Cardiac Center Lahore from 1st Jan to 1st June 2013. Mean fluoroscopy times via trans-radia (TR) and trans-femoral (TF) routes were compared. Procedure time was considered as time from sheath insertion to the finish of the diagnostic and interventional procedure. Descriptive statistics were used to explain the data. Chi square test was applied to compare qualitative variables between them. Results:A total of 1,110 diagnostic & PCI cases were performed out of which there were 850 diagnostic CA and 260 PCI cases. The mean procedure time & mean fluoroscopy time for TF-CA was 15.5±5.5 minutes and 4.3±3.2 minutes respectively in the current study while for TR-CA was 6.6±4.1. For TF-PCI, mean procedure time was 42.3±16.7 minutes, mean fluoroscopy time was 11.6±7.7 minutes & for TR-PCI it was 55.3±19.2 and 15.4±12.1.Conclusion: Radial route for cardiac catheterization procedures is associated with longer fluoroscopy time leading to increased radiation exposure to the operator along with an increased use of contrast.